The Dynamics Of Self-Concept Of Dual Instagram Account User (Public And Private Account) - Melati Wijayanti; Widhi Adhiatma (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2018)
The current study aimed at depicting the dynamics of self-concept of the Instagram user who possesses two accounts. The first account (public account) exhibits the user's identifiable identity, while the second account (private account) does not show the original identity of the user. The present study employed a narrative qualitative approach aiming at viewing the self-concept dynamics of dual account user. There were three samples who were selected by using purposive sampling. The data were collected by using an in-depth interview. The data were analyzed using data triangulation The finding of the study showed that in the public account, the participants would behave in accordance with self-image or impression they intend to build, while in private account, the participants did not attempt to create a positive self-image or impression. The present study can be used as a reference in understanding the self-concept of the dual social media account user.